Fatty acid‐binding protein 5 controls lung tumor metastasis by regulating the maturation of natural killer cells in the lung. Issue 13 (25th May 2021) - Yang, Shuhan; Kobayashi, Shuhei; Sekino, Kaname; Kagawa, Yoshiteru; Miyazaki, Hirofumi; Kumar Shil, Subrata; Abdulaziz Umaru, Banlanjo; Wannakul, Tunyanat; Owada, Yuji
Abstract : Fatty acid‐binding protein (FABP) 5 is highly expressed in various types of tumors and is strongly correlated with tumor growth, development, and metastasis. However, it is unclear how the expression of FABP5 in the host affects tumor progression. In this study, using a lung tumor metastasis model in mice, we found that FABP5‐deficient mice were more susceptible to tumor metastasis, which is accompanied by infiltration of a lower frequency of activated natural killer (NK) cells in the lung. Additionally, FABP5 deficiency leads to impaired maturation of NK cells in the lungs, but not in the bone marrow and spleen. Taken together, our results provide the first evidence that FABP5 in the host regulates lung tumor metastasis through controlling NK cell maturation. Abstract :